Current molecular understanding of central nervous system schwannomas - Takahiro Tsuchiya; Satoru Miyawaki; Yu Teranishi; Kenta Ohara; Yudai Hirano; Shotaro Ogawa; Seiei Torazawa; Yu Sakai; Hiroki Hongo; Hideaki Ono; Nobuhito Saito (Acta Neuropathologica Communications)
Abstract Background Schwannomas are tumors that originate from myelinating Schwann cells and can occur in cranial, spinal, and peripheral nerves. Although our understanding of the molecular biology underlying schwannomas remains incomplete, numerous studies have identified various molecular findings and biomarkers associated with schwannomas of the central nervous system (CNS). The development of these tumors is primarily linked to mutations in the NF2 gene. Merlin, the protein encoded by NF2, is integral to several signaling pathways, including Ras/Raf/MEK/ERK, PI3K/Akt/mTORC1, Wnt/β-catenin, and the Hippo pathway. Main body Recent research has also uncovered novel genetic alterations, such as the SH3PXD2A::HTRA1 fusion gene, VGLL-fusions in intraparenchymal CNS schwannomas, and the SOX10 mutation particularly in non-vestibular cranial nerve schwannomas. In addition to genetic alterations, research is also being conducted on gene expression and epigenetic regulation, with a focus on NF2 methylation and post-transcriptional silencing by micro RNA. Furthermore, the advent of advanced techniques like single-cell sequencing and multi-omics analysis has facilitated rapid discoveries related to the tumor microenvironment and tumor heterogeneity in schwannomas. Conclusion A deeper exploration of these molecular findings could clarify the mechanisms of schwannoma tumorigenesis and progression, ultimately guiding the development of new therapeutic targets. This review offers a comprehensive overview of the current molecular understanding of CNS schwannomas, emphasizing the insights gained from previous research, while addressing existing controversies and outlining future research and treatment perspectives.